The Application of Mind Mapping Learning Model in Recount Writing - Zusmizawati, Zusmizawati (Universitas Islam Negeri Raden Intan Lampung, 2019)
Most students at SMAN 8 Bandar Lampung, particularly those of X MIA 1 class, were struggling with English, including in recount writing lesson. The issue was most probably due to the fact that most of the students perceived English as a difficult and uninteresting subject. However, the findings show that the application of mind mapping learning model has increased the students’ learning interest, from 47.37% (n = 18) in the initial condition to 68.42% (n = 26) in the first cycle and 100% (n = 38) in the second cycle. The mind mapping method has also proved successfully in improving the learning outcomes. The students’ mean score on the posttest has improved from 57.37 in the initial condition to 64.21 in the first cycle and 73.16 in the second cycle, with a learning completion rate21.05% (n = 8) in the initial condition, to 52.63% (n = 20) in the first cycle and 89.47% (n = 34) in the second cycle. Despite four underachieving students by the end of the second cycle (10.53%), all indicators and criteria for successful improvement of learning process have generally been satisfied.